Measurement of the B0→π−ℓ+ν and B+→η(')ℓ+ν branching fractions, the B0→π−ℓ+ν and B+→ηℓ+ν form-factor shapes, and determination of |Vub| - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We report the results of a study of the exclusive charmless semileptonic decays, B+→η(')ℓ+ν and B0→π−ℓ+ν, undertaken with approximately 464×106 BB[bar] pairs collected at the Υ(4S) resonance with the BABAR detector. The analysis uses events in which the signal B decays are reconstructed with a loose neutrino reconstruction technique. We obtain partial branching fractions for B+→ηℓ+ν and B0→π−ℓ+ν decays in three and 12 bins of q2, respectively, from which we extract the f+(q2) form-factor shapes and the total branching fractions B(B+→ηℓ+ν)=(0.36±0.05stat±0.04syst)×10−4 and B(B0→π−ℓ+ν)=(1.42±0.05stat±0.07syst)×10−4. We also measure B(B+→η′ℓ+ν)=(0.24±0.08stat±0.03syst)×10−4. We obtain values for the magnitude of the CKM matrix element |Vub| using three different QCD calculations.
*BABAR Collaboration: P. del Amo Sanchez, J. Marks, U. Uwer [und 432 weitere Personen]
Im Titel sind die Zahl 0 und die Plus- und Minuszeichen hochgestellt
Im Titel ist der Ausdruck "(')" hochgestellt
Im Titel ist der Ausdruck "ub" tiefgestellt
Gesehen am 05.10.2022